Challenges of the Latin-American Theology of Liberation to the Global North - Tamayo, Juan José (2019)
The Theology of Liberation has been a sign of contradiction that bothered certain sectors of the ecclesial and civil institution of our society. Despite fierce opposition and ruthless accusations, the theology of liberation was consolidated in history, as a theology that is presented as intercultural, interreligious and inter-ethnic in a community setting.The Theology of Liberation has as reference the culture of austerity, of the defense of human rights and of the earth. It develops in a cosmocentric vision, in a history conceived as captivity, but focused on liberation.The reason is compassionate and practical of the yearning memory, open to hope and anamnestic reason, which builds a liberating spirituality, for an intercultural and fraternal Christianity. The Theology of Liberation is not dead, it is alive and it is a great theological contribution for our time.